A non-covalent strategy for montmorillonite/xylose self-healing hydrogels. Issue 51 (5th June 2015) - Qi, Xianming; Guan, Ying; Chen, Gegu; Zhang, Bing; Ren, Junli; Peng, Feng; Sun, Runcang
<x xml:space="preserve">Abstract</x> The self-healing capability of hydrogels has become a hot topic in the area of hydrogel research.